Duration in power and happiness in the world - Désiré Avom; Itchoko M. M. Mwa Ndjokou; Pierre C. Tsopmo; Cherif Abdramane; Simplice Asongu (African Governance and Development Institute (AGDI), 2024)
This article examines the effect of leader longevity in power on world happiness. To make the assessment, a sample composed of 135 countries observed over the period 2006 to 2018 was constituted. The results obtained from OLS estimates show that longevity in power reduces individual happiness. Furthermore, the negative effect is more amplified in democratic countries. Quantile regression reveals variability in the effect over the different intervals. These results are robust to the use of alternative estimation techniques. We also identify the quality of institutions and public spending as two potential transmission channels through which longevity in power influences well-being. These results invite political authorities to respect constitutional limits or implement constitutional reforms with the aim of limiting the duration of the mandate of the executive in order to reduce the harmful effect of an extension of the latter on individuals' well-being.
Keywords: D72; H31; H52; I31; 330; longevity in power; happiness; quality of institutions; public spending; quantile regression